Punch, or the London Charivari, Volume 108, February 2, 1895 - Various; Burnand, F. C. (Francis Cowley), 1836-1917 (Salt Lake City, UT : Project Gutenberg, 2014)
"Punch, or the London Charivari, Volume 108, February 2, 1895" by Various is a satirical periodical from the late 19th century. This collection features a series of humorous articles, illustrations, and sketches that reflect the social, cultural, and political climate of the time, using wit and satire to comment on contemporary events and trends. The book likely encapsulates the essence of Victorian humor and commentary, offering insight into the attitudes and entertainments of that era. The content within the issue includes a mix of satirical stories and poems, such as "The Pink Hippopotamus," which follows a ludicrous adventure involving a father bound by ropes amidst wild animals, highlighting absurdity and humorous storytelling. Additionally, playful editorials on sports, gender roles in sports commentary, and whimsical interactions among various characters showcase the lighthearted take on serious societal themes. The publication uses clever wordplay, absurd scenarios, and engaging illustrations, making it an entertaining read that captures the playful spirit of its time while also inviting readers to reflect on the quirks and follies of daily life. (This is an automatically generated summary.)
Release date is 2014-03-10
E-text prepared by Lisa Tang, Malcolm Farmer, and the Online Distributed Proofreading Team
Keywords: English wit and humor -- Periodicals